Harnessing bioluminescence for drug discovery and epigenetic research - Gleneadie, Hannah J.; Dimond, Andrew; Fisher, Amanda G. (Frontiers in Drug Discovery, 2023)
The naturally occurring phenomenon of bioluminescence has intrigued on-lookers for decades and is now being developed as a powerful tool for medical research and preclinical imaging. Luciferase enzymes emit light upon substrate encounter, enabling their activity to be visualised and dynamically tracked. By inserting luciferase genes into specific sites in the genome, it is possible to engineer reporters to monitor gene expression in its native context, and to detect epigenetic change in vivo. Endogenous bioluminescent reporters provide a highly sensitive, quantitative read-out of gene expression that is both well suited to longitudinal studies and can be adapted for high-throughput drug screens. In this article we outline some of the applications and benefits of bioluminescent reporters for epigenetic research, with a particular focus on revealing new therapeutic options for treating genetic and epigenetic disorders.